Os colonos do papel : trabalhadores pluriativos no Oeste de Santa Catarina - o caso de Faxinal dos Guedes-SC - 1990-2006 - Basquera, Claudemir (2007)
The work analyzes the question of the pluriatividade in the catarinense agricultural way, having as case study the phenomenon them colonist-laborers it West of Santa Catarina, using itself as starting point an examination of the conjuncture of familiar agriculture in the city of Faxinal dos Guedes and its transformations, changing the direction of understanding it peasant and its relations in the agricultural way. Specifically, it is aimed at to investigate the description of the small average e property in the state of Santa Catarina, to discourse on the existing problems in these, as well as the occured changes in the last years, to discover what it takes the small average e proprietor to unite the work in its lands to the wage-earning work and in the same line of thought, to perceive the changes in the economic and social life of these families and the involved community